Plasma osteoprotegerin predicts adverse cardiovascular events in stable coronary artery disease: the PEACE trial - Ma, Teng; Zhao, Jian; Yan, Yechao; Liu, Junying; Zang, Jie; Zhang, Yaqi; Ruan, Kun; Xu, Hong; He, Wan (Frontiers in Cardiovascular Medicine, 2023)
Background Osteoprotegerin (OPG) is a secretory glycoprotein and participates in the progression of atherosclerotic lesions. We aim to explore the relationship between OPG and the prognosis of coronary artery disease (CAD). Methods Plasma OPG concentrations were measured in 3,766 patients with stable CAD enrolled in the PEACE trial. The PEACE trial (NCT00000558) group followed up the patients and examined their future clinical outcomes. Results In summary, 208 (5.5%) primary outcomes occurred, 295 patients (7.8%) died from all-cause death, 128 (3.4%) died from cardiovascular causes, and 94 (2.5%) experienced heart failure during a median follow-up of 1,892 days. In addition, we found that higher plasma levels of OPG were associated with a higher incidence of all-cause death, cardiovascular death, and heart failure, even after adjusting clinical cofounders. Conclusion It was demonstrated that elevated plasma OPG levels were associated with an increased incidence of all-cause death, cardiovascular death, and heart failure in patients with stable CAD. Systematic Review Registration https://clinicaltrials.gov/ct2/show/NCT00000558?term=NCT00000558&draw=2&rank=1, identifier: NCT00000558.